Evaluation of agronomic performance and fiber quality of cultivars and strains of glandless cotton grown in the conditions of Minas Gerais, Brazil - Penna, Julio Cesar Viglioni; Torres, Giovana Augusta (Pesquisa Agropecuaria Brasileira, 1994)
This research had the objective of evaluating agronomic performance, as well as fiber properties, of a group of seven upland cotton glandless cultivars and strains, grown in the conditions of Minas Gerais State, Brazil, in order to obtain information as for the direct utilization of such materials as a crop, or its improvement in breeding programs. The germplams tested were obtained from the main Gossypium collections maintained in the country, although this work did not evaluate all existing entries, but the available ones. This study revealed specifically two strains, G 4960 and G 4953, which presented overall agronomic performance and fiber traits considered similar to the check treatment, cultivar IAC 20. Some considerations are made as for future research needs before large scale cultivation of glandless cottons is recommended in the conditions tested.